China's emergence in the world economy and business cycles in Latin America - Ambrogio Cesa-Bianchi; M. Hashem Pesaran; Alessandro Rebucci; TengTeng Xu (Institute for the Study of Labor (IZA), 2011)
The international business cycle is very important for Latin America's economic performance as the recent global crisis vividly illustrated. This paper investigates how changes in trade linkages between China, Latin America, and the rest of the world have altered the transmission mechanism of international business cycles to Latin America. Evidence based on a Global Vector Autoregressive (GVAR) model for 5 large Latin American economies and all major advanced and emerging economies of the world shows that the long-term impact of a China GDP shock on the typical Latin American economy has increased by three times since mid-1990s. At the same time, the long-term impact of a US GDP shock has halved, while the transmission of shocks to Latin America and the rest of emerging Asia (excluding China and India) GDP has not undergone any significant change. Contrary to common wisdom, we find that these changes owe more to the changed impact of China on Latin America's traditional and largest trading partners than to increased direct bilateral trade linkages boosted by the decade long commodity price boom. These findings help to explain why Latin America did so well during the global crisis, but point to the risks associated with a deceleration in China's economic growth in the future for both Latin America and the rest of the world economy. The evidence reported also suggests that the emergence of China as an important source of world growth might be the driver of the so called decoupling of emerging markets business cycle from that of advanced economies reported in the existing literature.
urn:nbn:de:101:1-201108093198
Keywords: C32; F44; E32; O54; 330; China; GVAR; Great Recession; emerging markets; international business cycle; Latin America; trade linkages